The influence of temperature on viscoelastic friction properties - Putignano,C; Reddyhoff,T; Dini,D (Tribology International, 2016)
Viscoelastic friction strongly depends on temperature, which determines the material stiffness and, therefore, given a constant load, the volume that is deformed and dissipates energy. We compare the results obtained by a numerical approach introduced by Carbone and Putignano (2013) [1] with measurements that separate viscoelastic losses from Coulomb contribution. This is done for a range of temperatures. We show that viscoelastic friction curves for different temperatures can be arranged into a single master curve using a frequency shift coefficient, which can be found from the characterization of the viscoelastic material response. This shows that it is possible to accurately (a) use dynamic material analysis data to extrapolate viscoelastic friction measurements to values outside the tested range, and (b) use a tribometer to obtain fundamental viscoelastic material properties.